Complex hepatic injury involving a liver transplant recipient: A case report and review of literature. (2016) - Gray, Sanjiv; Shiek, Fariha; Shiber, Joseph
Highlights: Multidisciplinary approach is required to improve the morbidity and mortality of complex liver injuries AAST grades IV and V. Angioembolization is an essential adjunct in the management of complex liver injuries. Injuries to a transplanted liver warrant special consideration to the early involvement of a transplant surgeon.